Globalization and the nutrition transition: A case study - Hawkes, Corinna (Cornell University, 2007)
In the current “nutrition transition,” the consumption of high-calorie, nutrient-poor foods high in fats and sweeteners is increasing throughout the developing world. The nutrition transition, implicated in the rapid rise of obesity and diet-related chronic diseases worldwide, is rooted in the processes of globalization. Globalization affects the nature of the food supply chain, thereby altering the quantity, type, cost, and desirability of foods available for consumption. Understanding the links between globalization and the nutrition transition can thus help policy makers develop policies, including food policies, for addressing the global burden of chronic disease.; This case study explores how one of the central mechanisms of globalization, the integration of the global marketplace, is affecting specific food consumption trends in the context of the nutrition transition. Focusing on middle-income countries, it highlights the importance of three major processes of market integration: the production and trade of agricultural goods, foreign direct investment in food processing and retailing, and global food advertising and promotion.; This case study explores how one of the central mechanisms of globalization, the integration of the global marketplace, is affecting specific food consumption trends in the context of the nutrition transition. Focusing on middle-income countries, it highlights the importance of three major processes of market integration: the production and trade of agricultural goods, foreign direct investment in food processing and retailing, and global food advertising and promotion.; It finds that policies and processes designed to advance the globalization of the world economy in the areas of agriculture, trade, investment, and marketing are shaping dietary trends. Thus the policies designed to integrate the global food market matter for what people eat. Dietary outcomes also depend on the socioeconomic and cultural context in which the policies are operating, as well as changes in consumer behavior.; The dynamic, competitive forces unleashed as a result of globalization facilitate not only convergence in consumption habits (“Coca-Colonization”), but also adaptation to products targeted at different niche markets. This convergence-divergence duality raises the policy concern that globalization will exacerbate uneven dietary development between rich and poor. As high-income groups in developing countries accrue the benefits of a more dynamic marketplace, lower-income groups may well experience convergence toward poor-quality obesogenic diets, as observed in Western countries.; Health policy makers should pay greater attention to globalization processes and policies in order to address some of the structural causes of obesity and diet-related chronic diseases worldwide, especially among groups with low socioeconomic status. The benefit of leveraging policies designed to integrate global food markets to encourage healthy diets is that relatively small changes at a macro-scale can have relatively large population-wide impacts.; Your assignment is to advise a government of a middle-income developing country about appropriate policies to mitigate the negative effects of the nutrition transition in the context of globalization, taking into account the interests of the various stakeholder groups.